Challenges in the Management of Wilms Tumor in a Developing Country: A Twenty Years' Experience From a Single Center in Pakistan. Issue 8 (3rd November 2022) - Khan, Muhammad Rahil; Maaz, Ata Ur Rehman; Ashraf, Muhammad Shamvil
Abstract : Background: Wilms Tumor (WT) is one of the most curable childhood cancers. High cure rates seen in the developed countries are not reproduced in developing countries. Lack of access to cancer treatment facilities, financial constraints, late presentation, and abandonment have previously been described. We reviewed our data over the last 20 years to highlight some of these challenges. Methods: This is a retrospective chart review of children with WT at our center up to the age of 18 years between 1 November 1997 and 30 November 2017. Demographic details, presentation characteristics and treatment details were recorded. Factors associated with poor outcome were analyzed. Results: Two hundred eleven children were registered; 117(55.5%) were males. Median age at presentation was 3 (range 0 to 18) years. Presentation data were available for 184/211 patients, staging details for 159/211 and metastatic status for 178/211. Of the available dataset, 60% presented without prior treatment, whereas 40% presented atleast after primary surgical excision. High-stage (stage III or above) disease was present in 79 (49.7%) patients; 61 (34.3%) was presented with metastases or recurrence; 63 (29.8%) abandoned or refused treatment; 99/172 (57.6%) patients finished treatment, 23 (13.4%) died during treatment, and 6 died before treatment. Of the 99 patients who finished treatment 83 (83.8%) are well off therapy; 15(15.2%) relapsed; 6 (40%) are alive after salvage therapy, while 9 (60%) died. Conclusions: Our data highlights the challenges of managing WT in resource poor environments. Prior surgery, incomplete staging work-up and abandonment are some of the most frequently encountered barriers. A multipronged approach is required to overcome these challenges.